Kerion caused by Microsporum audouinii in a child - Fernandes, Sónia (Elsevier, 2013)
Kerion celsi is rarely associated with Microsporum audouinii infection. We report the case of a 3-year-old girl with a kerion celsi caused by M. audouinii and successfully treated with oral terbinafine. Fungi identification was made by macro and microscopical colony morphology analyses and molecular (genotypic) studies.